EFEKTIVITAS APLIKASI TEPUNG DAUN SIRSAK DENGAN BERBAGAI DOSIS BOKASHI TERHADAP PENYAKIT LAYU FUSARIUM PADA TANAMAN TOMAT (Solanum lycopersicum L.) - KHAERUNI, ANDI; HEMI, WA; HASAN, ASMAR; HS, GUSNAWATY; SYAIR, SYAIR; SATRAH, VIT NERU (Jurnal Agroteknos, 2024)
Tomato (Solanum lycopersicum L.) is a vegetable commodity whose market demand continues to increase from year to year, so it requires good cultivation management so that the quantity and quality of tomatoes also continues to increase. One of the reasons for the less than optimal production of tomatoes is caused by the fungus Fusarium spp. This study aims to determine the Effectiveness of Soursop Leaf Powder Application with Various Doses of Bokashi Against Fusarium Wilt Disease in Tomato (Solanum lycopersicum L.). This research was conducted at the Plant Protection Laboratory of the Phytopathology and Land Unit I (one) Faculty of Agriculture, Halu Oleo University, Kendari from October 2022 to January 2023 using a Completely Randomized Design (CRD) Factorial 2 Factors. The first factor was soursop leaf powder (T) consisting of control (T0), 50 g soursop leaf powder (T1), 75 g soursop leaf powder (T2). The second factor was bokashi fertilizer consisting of control (B0), 500 g bokashi fertilizer (B1) and 500 g bokashi fertilizer (B2). Thus, 9 treatments were obtained, and each treatment was repeated 3 times to obtain 27 experimental units. The variables observed were the incubation period, disease severity, AUDPC and disease suppression index. The best disease severity interaction was found in the T2B2 treatment with an average disease severity of 33.33%. The effect of the interaction application treatment had a very significant effect on the treatment of soursop leaf flour and bokashi fertilizer with an average incubation period of 63.33% HSI